The Relationship between Islamic Religious Knowledge and the Behavior of High School Students - Kholia Eka Putri; Syukri Amin (At-Ta'lim : Media Informasi Pendidikan Islam, 2024)
ENGLISH: The Relationship between Islamic Religious Knowledge and the Behavior of High School StudentsObjective: This study aims to determine whether there is a relationship and reveal how much influence Islamic religious knowledge has on student behavior at SMA Negeri 6 Seluma. Method: The research design used a quantitative approach (correlation study); this research was conducted at SMA Negeri 6 Seluma in 2024; the research subjects were second-grade students totaling 41. Questionnaire instruments were used as data collection tools. Data analysis uses a normality test, correlation test, and determination coefficient using the product moment correlation technique. Result: students' Islamic religious knowledge level is in the high category, with an average score of 82.7. Meanwhile, student behavior is in the moderate category, with an average score of 48.3. Conclusion: Students with high Islamic religious knowledge do not guarantee good behavior, and students with low Islamic religious knowledge do not guarantee bad behavior because that is not the factor that affects behavior; other factors outside this variable affect it. Contribution: This research can be used as a source of scientific information about the relationship between religious education and student character building, especially in the context of high schoolINDONESIAN: Hubungan antara Pengetahuan Agama Islam dan Perilaku Siswa tingkat SMATujuan: Penelitian ini bertujuan untuk mengetahui apakah ada hubungan dan mengungkapkan seberapa besar pengaruh pengetahuan agama Islam terhadap perilaku siswa di SMA Negeri 6 Seluma. Metode: Desain penelitian menggunakan pendekatan kuantitatif (studi korelasi), Penelitian ini dilaksanakan di SMA Negeri 6 Seluma tahun 2024, Subjek penelitian yaitu siswa kelas dua berjumlah 41. Instrumen angket digunakan sebagai alat pengumpulan data. Anaslisis data menggunakan uji normalitas, uji korelasi, dan koefisien determinasi menggunakan teknik korelasi product moment. Hasil: tingkat pengetahuan agama Islam siswa berada pada kategori tinggi, dengan rata-rata nilai sebesar 82,7. Sementara itu, perilaku siswa berada pada kategori sedang, dengan rata-rata skor 48,3. Kesimpulan: siswa yang berpengetahuan agama Islam tinggi tidak menjamin berperilaku yang baik dan siswa yang pengetahuan agama Islam rendah tidak menjamin berperilaku yang buruk karena bukan itu faktor yang mempengaruhi perilaku, akan tetapi ada faktor lain diluar variabel ini yang mempengaruhinya. Kontribusi: penelitian ini dapat dijadikan sebagai sumber informasi ilmu pengetahuan tentang hubungan pendidikan agama dan pembentukan karakter siswa, khususnya dalam konteks sekolah menengah atas.